Pengaruh Kualitas Produk Terhadap Minat Beli Konsumen Pada Home Industri Pia Deisy Desa Kapitu Kecamatan Amurang Barat - Karundeng, Nikita; Kalangi, Johny A. F.; Walangitan, Olivia Ch. F. (JURNAL ADMINISTRASI BISNIS, 2019)
This study aims to determine whether Product Quality has an effect on Consumer BuyingInterest. Speaking with quality and buying interest is certainly very tied to marketing. Theessence of marketing according to Daryanto (2011) "marketing is a social and managerialprocess where individuals and groups get their needs and desires by creating, offering, andexchanging something of value with each other". This type of research is quantitativeresearch with data analysis techniques using a skla likert research instrument, test validity,reliability, simple linear regression analysis and hypothesis testing. Based on the results ofthe study the influence of product quality is a variable that does not affect consumer buyinginterest. Then it can be concluded that product quality does not significantly influenceconsumer buying interest. If the quality of the product is good, there will be buying interestand consumers will feel satisfied. In this case, Pia Deisy's business must further improveproduct quality so that it will be more attractive and will have a good impact on Pia Deisy'shome business.